Optimalizační úlohy na bázi částicových hejn (PSO) - Němeček, Patrik (Vysoké učení technické v Brně. Fakulta informačních technologií, 2014)
Práce se zabývá optimalizací na bázi částicových hejn. V teoretické části je nejprve stručně popsána problematika optimalizace. Poté se značná část věnuje celkovému popisu optimalizačního algoritmu na bázi částicových hejn (PSO). Jsou popsány jeho princip, chování, parametry, struktura a modifikace. Následuje rešerše variant PSO, včetně hybridizací PSO. V praktické části práce jsou nejprve blíže rozebrány dynamické problémy. Poté je popsán nově navržený algoritmus pro dynamické problémy AHPSO (z čeho vychází, čím byl inspirován a jaké prvky používá a proč). Algoritmus je spuštěn na sadě úloh (Moving peaks benchmark) a porovnán s dosud nejlepšími veřejně dostupnými algoritmy variant PSO na dynamické problémy.

This work deals with particle swarm optimization. The theoretic part briefly describes the problem of optimization. The considerable part focuses on the overall description of particle swarm optimization (PSO). The principle, behavior, parameters, structure and modifications of PSO are described. The next part of the work is a recherché of variants of PSO, including hybridizations of PSO. In practical part the dynamic problems are analyzed and new designed algorithm for dynamic problems AHPSO is described (what it is based on, what was inspired, what elements are used and why). Algorithm is executed on the set of tasks (Moving peaks benchmark) and compared with the best publicly available variants of algorithm PSO on dynamic problems so far.
PSO-Particle Swarm Optimization
Keywords: Optimalizace na bázi částicových hejn; varianty a hybridizace PSO; dynamické problémy; Moving peaks benchmark; AHPSO.; Particle Swarm Optimization; PSO variants and hybridizations; dynamic problems; Moving peaks benchmark; AHPSO.